Are we deskilling or reskilling our hospital ward clinicians?. Issue 4 (5th April 2023) - Bunch, Jacinda; Jones, Daryl; Psirides, Alex
Abstract: Rapid reponse teams emerged 27 years ago to identify deteriorating patients and reduce preventable harm. There are concerns that such teams have deskilled hospital staff. However, over the past 20 years, there have been marked changes in hospital care and workplace requirements for hospital staff. In this article, we contend that hospital staff have been reskilled rather than deskilled.